Measuring service quality in Samarahan district office/ Khatijah Reduan, Laura Peritha Tupi& Faizah Mazlan Tajuddin - Reduan, Khatijah; Tupi, Laura Peritha; Tajuddin, Faizah Mazlan (2011)
The services provides by Samarahan District Office (SDO) is a type of public services that are important for their local people in order to give advantages and administrating their local people needs. The project paper covers the measurement of the quality of services provided by SDO’s services. These SDO service quality related to the characteristic by namely, organisation, product or services is judge by the clients. The good quality services provided by SDO can only be achieved with the existence of excellent staffs in different level or fields from aspect of knowledgeable, expert in work, discipline and committed in their work and productive. The purposed of the research is about the service quality in SDO by measuring the quality level of-service provided by the staffs to the SDO’s customers. The project paper also simply identified the level of achievement of the SDO services towards their customer in a standard of the quality service. The level or timeline use by the SDO itself in delivering their services is difference and based on their customer charter. This project paper makes studies on their service quality from both internal and external customer of SDO in order to gained the result of the services either good service quality or not.